(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the historical, political, and geopolitical place of the Kurdish factor in Turkey’s foreign policy. Covering the period from the Ottoman era to the present day, it examines the Treaty of Lausanne, the emergence of the PKK, the Adana Protocol (1998), and Ankara’s policy toward the Kurdish structures in Syria and Iraq. The Kurdish factor is analyzed, on the basis of the theories of “dual-track diplomacy” and “securitization,” as simultaneously a security threat to Turkey and an important diplomatic-economic instrument. It is shown that Turkey actively uses this factor to pursue its strategic aims at the regional and international levels.